Psychoeducational Service for Competition Athletes in Paraná (SPAC-PR): Program implementation proposal cognitive stimulation - Puquevis Souza, Jaqueline; Costa Lobo, Cristina (Guará Journal, 2019)
The development of athletic talent currently prioritizes a holistic perspective that advocates the interaction between multiple factors. The importance and association of psychological variables with high-performance athletes have been widely demonstrated. The analysis of the psychological architecture of talented athletes and the development of indicators of access to excellence constitute a territory where Educational Psychology and Sports Psychology intersect. With the stated purpose of implementing cognitive stimulation programs that develop the specific needs of talented athletes in the state of Paraná, we present the permanent extension project called Psychoeducational Service for Competitive Athletes of Paraná: SPAC-PR. This article highlights the theoretical models of athletic development and describes and outlines the constituent axes of SPAC-PR, a service currently being implemented.